INFLUENCE OF METAL IONS BINDING ON FREE RADICAL CONCENTRATION IN HUMIC ACIDS. A QUANTITATIVE ELECTRON PARAMAGNETIC RESONANCE STUDY - Jerzykiewicz M.; Jezierski A.; Czechowski F.; Drozd J. (My University, 2002)
The influence of metal ions, e.g. Co(II), Cu(II), Mn(II), Ni(II), Fe(II), on free radical concentration in humic acids isolated from soil, peat and compost was investigated by electron paramagnetic resonance (EPR). The results show that metal ions with unfilled d-shell exhibit antiferromagnetic interactions with semiquinone radicals. Moreover, coordinated metals shift the quinone-semiquinone-hydroquinone equilibrium in the macromolecular matrix of humic acids. A strong decrease of semiquinone radical concentration in humic acid-metal complexes is observed. This effect is caused by interactions of metal ions with oxygen-containing stable radicals occurring in the aromatic systems of humic acids. Furthermore, the effect of metal coordination on free radical concentration in humic acids-metal complexes depends on the humic acid origin. FTIR spectroscopy was also used as an additional tool for studies of the metal ions interactions with carboxylic groups.